Evaluation of Relationship of Vegetation Dynamics with Seasonal Climate Evolution in Sheikh Badin National Park, Pakistan - Fatima, Naheed; Kausar, Rukhsana; Ashraf, Arshad; Arif, Muhammad; Noor, Rubina; Uz Zaman, Iftikhar (International Journal of Environment, 2024)
Climate change and other biotic factors are causing desertification and degradation of the range resources at an alarming rate especially in the arid and semiarid regions worldwide. The mountain region of Sheikh Badin National Park (SBNP) –famous for its floristic composition and biodiversity, is facing serious consequences of climate and anthropogenic effects in Pakistan. The influential role of extreme climate changes needs to be explored to mitigate growing risk of degradation of natural vegetation and biological resource in this mountain region. In the present study, relationship of NDVI (Normalized Difference Vegetation Index) was investigated with seasonal LST (Land Surface Temperature), and TRMM (Tropical Rainfall Measurement Mission rainfall) rainfall of 2000-2018 period in the SBNP, Khyber Pakhtunkhwa province of Pakistan for sustaining ecosystem health. The findings of the study revealed increasing trends in NDVI during winter, spring, summer and autumn with corresponding increase in rainfall in the study area. The correlation coefficient R value between NDVI and LST was found -0.37 for winter, -0.72 for spring, -0.002 for summer and -012 for autumn (significant at p<0.05). The correlation between NDVI and rainfall revealed R values 0.41, 0.79, 0.64 and 0.7 for winter, spring, summer and autumn seasons (significant at p<0.05), respectively. The rainfall appears to be a major determinant of vegetation health and consequent ecosystem sustainability in the study area. However, the seasonal changes in climate and their implications necessitate adoption of integrated management of ecosystem to conserve biological resource on sustainable basis in this region in future.